2022
DOI: 10.1038/s41422-022-00652-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic nucleosome organization after fertilization reveals regulatory factors for mouse zygotic genome activation

Abstract: Chromatin remodeling is essential for epigenome reprogramming after fertilization. However, the underlying mechanisms of chromatin remodeling remain to be explored. Here, we investigated the dynamic changes in nucleosome occupancy and positioning in pronucleus-stage zygotes using ultra low-input MNase-seq. We observed distinct features of inheritance and reconstruction of nucleosome positioning in both paternal and maternal genomes. Genome-wide de novo nucleosome occupancy in the paternal genome was observed a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 62 publications
4
32
0
Order By: Relevance
“…The lengths of the mapped reads were mainly enriched at approximately 147 bp, which is the DNA size in mononucleosomes ( Figure S1 D). After fertilization, the nucleosome occupancy of the paternal genome undergoes a dramatic increase, while this rapid de novo establishment process does not occur in the maternal genome ( Wang et al., 2022 ). Similar to female pronuclei (PN) in fertilized embryos, the nucleosome occupation rate showed little change, and the enrichment of nucleosomes on different genomic elements was also relatively stable during SCNT embryonic development ( Figures S1 F and S1G).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The lengths of the mapped reads were mainly enriched at approximately 147 bp, which is the DNA size in mononucleosomes ( Figure S1 D). After fertilization, the nucleosome occupancy of the paternal genome undergoes a dramatic increase, while this rapid de novo establishment process does not occur in the maternal genome ( Wang et al., 2022 ). Similar to female pronuclei (PN) in fertilized embryos, the nucleosome occupation rate showed little change, and the enrichment of nucleosomes on different genomic elements was also relatively stable during SCNT embryonic development ( Figures S1 F and S1G).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the NDRs and precisely positioned +1 and −1 nucleosomes around TSSs disappeared as early as 1 hpi and were rebuilt until 6 h after activation of the SCNT embryos ( Figure 1 B). However, the NDR pattern around TSSs appears much earlier in fertilized embryos, with male PN at 1.5 h post-fertilization (hpf) and female PN at 3 hpf ( Wang et al., 2022 ). Previous studies have shown that nucleosome arrangement is associated with the cell cycle, with fuzzier organization during S and M phases ( Deniz et al., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations